The technopolitics of hydrogen: Arab Gulf States’ pursuit of significance in a climate-constrained world - Zumbrägel, Tobias (Geoforum, 2025)
Despite uncertainties surrounding the hydrogen economy’s emergence in terms of technological innovation, production, storage and transport, policy and regulation, economic viability, and environmental impact, countries worldwide actively pursue initiatives to engage in this critical energy transition. Politicians, analysts, and global experts see ‘clean’ hydrogen as the ultimate solution for addressing the climate crisis. This optimism is shared by several major oil and gas-exporting nations, which are investing heavily in hydrogen infrastructure to establish themselves as future global hubs. Oman, Saudi Arabia, and the United Arab Emirates (UAE) are especially well-positioned, benefiting from strategic advantages over other hydrogen-producing regions in the Global South. Advocates in these countries view hydrogen as a potential ‘silver bullet’ for sustaining political and economic influence in a world increasingly shaped by climate constraints. Western technology and expertise play a significant role in supporting these efforts. By using various qualitative methods, this paper employs and expand the concept of technopolitics to evaluate the role of industrialized nations in endorsing the Gulf states’ authoritarian, top-down, techno-optimistic approach to their sustainability agenda.
Gesehen am 02.05.2025